Finding Customer Satisfaction and Loyalty Factors in Islamic Bank Digital Users - Ade Sofyan Mulazid; Fatmawati Fatmawati (Faculty of Economics UIN Maulana Malik Ibrahim Malang, 2023)
The study aims to investigate the influence of brand image, service quality, and trust on customer satisfaction and loyalty of Islamic bank digital users. This study uses primary data by distributing questionnaires to customers who have used Islamic bank digital applications. The research sample amounted to 100 respondents and used the purposive sample method. The method used in this study is Partial Least Square (PLS) using SmartPLS 3.0 data analysis tool. The results showed that brand image, service quality, and trust affect satisfaction. Brand image and service quality do not affect loyalty. Satisfaction affects loyalty. Brand image, service quality, and trust affect loyalty through customer satisfaction. This research provides a theoretical contribution to literature development as a pioneering effort to investigate the influence of brand image, service quality, and trust on customer satisfaction and loyalty of Islamic bank digital users. Managerial implications, Islamic banking seeks to develop facilities to improve customer service efficiency by implementing brand image, service quality and trust, thereby increasing customer satisfaction and loyalty.